Process selection from design to manufacture - Swift, K. G.; Booker, J. D. (Oxford [England] ; Boston : Butterworth-Heinemann, 2003)
The definitive practical guide to choosing the optimum manufacturing process, written for students and engineers. Process Selection provides engineers with the essential technological and economic data to guide the selection of manufacturing processes. This fully revised second edition covers a wide range of important manufacturing processes and will ensure design decisions are made to achieve optimal cost and quality objectives. Expanded and updated to include contemporary manufacturing, fabrication and assembly technologies, the book puts process selection and costing into the context of modern product development and manufacturing, based on parameters such as materials requirements, design considerations, quality and economic factors. Key features of the book include: manufacturing process information maps (PRIMAs) provide detailed information on the characteristics and capabilities of 65 processes and their variants in a standard format; process capability charts detailing the processing tolerance ranges for key material types; strategies to facilitate process selection; detailed methods for estimating costs, both at the component and assembly level. The approach enables an engineer to understand the consequences of design decisions on the technological and economic aspects of component manufacturing, fabrication and assembly. This comprehensive book provides both a definitive guide to the subject for students and an invaluable source of reference for practising engineers. * manufacturing process information maps (PRIMAs) provide detailed information on the characteristics and capabilities of 65 processes in a standard format * process capability charts detail the processing tolerance ranges for key material types * detailed methods for estimating costs, both at the component and assembly level.
Preface * Notation * Part 1:A Strategic View; The Problem; Manufacturing Information for Design; Product Introduction Processes; A Process Selection Strategy; Part 2: Selecting Candidate Processes; Introduction; PRIMA Selection; Manufacturing Processes; Surface Engineering Processes; Assembly Systems; Joining Processes; Process Information Maps (PRIMAs): Casting Processes; Sand Casting; Shell Moulding; Gravity Die Casting; Pressure Die Casting; Centrifugal Casting; Investment Casting; Ceramic Mould Casting; Plaster Mould Casting; Squeeze Casting; Plastic & Composite Processing; Injection Moulding; Reaction Injection Moulding; Compression Moulding; Transfer Moulding; Vacuum Forming; Blow Moulding; Rotational Moulding; Contact Moulding; Continuous Extrusion (Plastics); Forming Processes; Hot Forging; Rolling; Drawing; Cold Forming; Cold Heading; Swaging; Superplastic Forming; Sheet Metal Shearing; Sheet Metal Forming; Spinning; Powder Metallurgy; Continuous Extrusion (Metals); Machining Processes; Turning and Boring; Milling; Planing and Shaping; Drilling Broaching; Reaming; Grinding; Honing; Lapping; Nontraditional Machining Processes; Electrical Discharge Machining (EDM); Electrochemical Machining (ECM); Electron Beam Machining (EBM) Laser Bean Machining (LBM); Chemical Machining (CM); Ultrasonic Machining (USM); Surface Engineering Processes; Hot Dipping; HardFacing; Cladding; Thermal Spraying; Chemical Vapour Deposition (CVD); Physical Vapour Deposition (PVD); Electroplating; Chemical Coating; Mechanical Treatments; Chemical Treatments; Painting; Assembly Technologies; Feeding Devices; Transfer Mechanisms; Manual Assembly Systems; Flexible Assembly Systems; Dedicated Assembly Systems; Joining Processes; Tungsten Inert-gas Welding (TIB); Metal Inert-gas Welding (MIG); Manual Metal Arc Welding (MMA); Submerged Arc Welding (SAW); Electron Beam Welding (LBM); Plasma Arc Welding (PAW); Resistance Welding (Spot, Seam, Projection, Flash, Electro-slag; Solid State Welding (Cold, Diffusion, Explosive, Friction, Ultrasonic; Thermit Welding (TW); Gas Welding (GW); Brazing; Soldering; Thermoplastic Welding; Adhesive Bonding; Mechanical Fastening; Combining the Use of the Selection Matrices and PRIMAs; Manufacturing Processes; Surface Engineering Processes; Assembly Systems; Joining Processes; Part III -- Costing Designs; Introduction; Assembly Sequence Diagrams; Component Costing; Development of the Model; Basic Processing Cost (Pc); Relative Cost Coefficient (Rc); Material Cost (Mc); Model Validation; Component Costing Case Studies; Manual Assembly Costing; Development of the Model; Assembly Costing Case Studies; Concluding Remarks; Sample Questions for Students; References Bibliography; Appendices; Weld Joint Design; Blank Manufacturing Analysis Table; Guidelines for Assembly Orientated Design.
Includes bibliographical references (p. [309]-312) and index.
Keywords: Manufacturing processes -- Decision making; Decision support systems; Production planning; Production -- Planification; Electronic books